2000
DOI: 10.1046/j.1440-1738.2000.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations of the décollement/protodécollement zone and their implications: A 3‐D seismic inversion study of the northern Barbados accretionary prism

Abstract: We conducted a 3‐D seismic inversion study to investigate spatial variations of physical properties of the décollement zone (DZ) and protodécollement zone (PDZ) under the northern Barbados accretionary prism. Significant spatial variations of physical properties were observed in the PDZ seaward of the thrust front from the inversion data. The density generally increases southward with a few localized low‐density patches. A lower density commonly corresponds to a thicker PDZ, suggesting that the paleomorphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…Low taper, fluid‐rich subduction zone forearcs are often inferred to have weak basal surfaces, commonly observed as high‐amplitude, negative polarity décollement reflectors in seismic data suggesting reduced bulk density, increased porosity and likely increased pore fluid pressure [e.g., Moore et al , 1995; Zhao et al , 2000; Bangs et al , 2004]. Prism fault geometry analysis of Kukowski et al [2001] suggest that the décollement in the Makran is >3 times weaker than the overlying prism sediments, however they also note that the slight observed overpressure [ Fruehn et al , 1997] may only account for ∼30% of the inferred décollement weakness, with the remainder a function of lithology or fracturing.…”
Section: Discussionmentioning
confidence: 99%
“…Low taper, fluid‐rich subduction zone forearcs are often inferred to have weak basal surfaces, commonly observed as high‐amplitude, negative polarity décollement reflectors in seismic data suggesting reduced bulk density, increased porosity and likely increased pore fluid pressure [e.g., Moore et al , 1995; Zhao et al , 2000; Bangs et al , 2004]. Prism fault geometry analysis of Kukowski et al [2001] suggest that the décollement in the Makran is >3 times weaker than the overlying prism sediments, however they also note that the slight observed overpressure [ Fruehn et al , 1997] may only account for ∼30% of the inferred décollement weakness, with the remainder a function of lithology or fracturing.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Seismic reflection data have shown that the décolle-ment characteristics of the Nankai and Barbados accretionary prisms can be recognized on the basis of their reflection polarities, seismic velocities, and other seismic attributes [e.g., Moore and Shipley, 1993;Shipley et al, 1994;Bangs et al, 1996Bangs et al, , 1999Bangs et al, , 2004Zhao et al, 2000;Tsuji et al, 2005a]. These studies using seismic data have focused mainly on the décollement reflection only in order to reveal its characteristics including pore pressure, although some studies have used seismic velocity data to predict pore pressure distributions within some accretionary wedges: the Nankai accretionary prism [Tobin and Saffer, 2003], the Barbados accretionary prism [Westbrook, 1991;Hayward et al, 2003], and the Oregon accretionary prism [Cochrane et al, 1994].…”
Section: Introductionmentioning
confidence: 99%
“…(2000), based on 3D seismic inversion, suggested that the southward increase in density and thus strength of the proto‐décollement zone continues into the décollement. Zhao et al. (2000) further proposed that a stronger décollement zone is responsible for a larger prism taper, thus more horizontal shortening, in the southern part of the prism toe.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, those in the western part of the area show largely NNE‐trending lineations. Zhao et al. (2000), based on 3D seismic inversion, suggested that the southward increase in density and thus strength of the proto‐décollement zone continues into the décollement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation